Sources of resistance of different cotton genotypes against bacterial blight disease incited by Xanthomonas axonopodis pv. malvacearum under natural epiphytotics - P. Jagtap, G.; M. Jangam, A.; Utpal, D. (Scientific Journal of Medical Science, 2013)
Atotal thirty-six cotton genotypes were screened in replicated thrice withRandomized Block Design against bacterial blight disease incited by Xanthomonasaxonopodis pv. malvacearum under natural epiphytotics. Resultsrevealed that 3 genotypes showed moderately resistant, 31 showed moderatelysusceptible and 2 showed susceptible against bacterial blight of cotton. Disease severity at 60 DAS ranged from 2.42 to 27.5 per cent, PH 1009(2.42 per cent), Paig 29 (2.42 per cent) had shown lowest diseaseseverity. Disease severity at 90 DASranged from 9.63 to 58.6 per cent. NH633 (9.63 per cent) had shown minimum disease severity followed by PH 1062 (9.91per cent) and PH 1031 (10.37 per cent). Disease severity at 120 DAS ranged from 11.63 to 68.94 per cent. The lowest PDI was recorded by NH 633 (11.63%) followed by Paig 265 (13.26 %) and NH 637 (13.55 %). Mean disease severity(PDI) of cotton genotypes was recorded in range 9.71 to 51.68 per cent.